2013
DOI: 10.1590/0104-1169.3060.2360
|View full text |Cite|
|
Sign up to set email alerts
|

Body composition of chronic renal patients: anthropometry and bioimpedance vector analysis

Abstract: OBJECTIVE: to compare the body composition of patients undergoing hemodialysis with that of healthy individuals using different methods. METHOD: cross-sectional study assessing male individuals using anthropometric markers, electrical bioimpedance and vector analysis. RESULTS: the healthy individuals presented larger triceps skinfold and arm circumference (p<0.001). The bioimpedance variables also presented significant higher values in this group. Significant difference was found in the confidence interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
3
0
3
Order By: Relevance
“…The average values of UAMA have been shown to be higher in men than in women in other studies; however, the absolute values of this research were lower than the values found in other national and international studies. [23][24][25][26] Stevenson et al 10 used quantitative peripheral computed tomography to compare the bones and skeletal muscle of NF1 patients and volunteers not affected by the disease. This study demonstrated that children with NF1 have lower muscle cross-sectional area than their controls, but this did not lead to major advances in the pathophysiology of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The average values of UAMA have been shown to be higher in men than in women in other studies; however, the absolute values of this research were lower than the values found in other national and international studies. [23][24][25][26] Stevenson et al 10 used quantitative peripheral computed tomography to compare the bones and skeletal muscle of NF1 patients and volunteers not affected by the disease. This study demonstrated that children with NF1 have lower muscle cross-sectional area than their controls, but this did not lead to major advances in the pathophysiology of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Promising alternate approaches to standard BIA include using the derived Xc and R for vector analysis or phase angle (φ) measurement. BIA phase angle has some prognostic utility for people with CKD and may reflect diminished muscle composition or lower body cell mass as a function of age or pathology [ 45 , 59 ].…”
Section: Clinically Viable Approaches To Assessing Changes In Skeletamentioning
confidence: 99%
“…However, important limitations exist regarding body composition estimates using BIA for those with altered states of hydration. Estimates of LBM include extracellular water and BIA may overestimate hydration levels and LBM prior to hemodialysis in patients with end-stage renal disease [ 18 ]. While both multi-frequency and single-frequency BIA may be used to estimate LBM in people with renal dysfunction, multi-frequency BIA with segmental analysis may be preferred when making distinctions among total body water, extracellular water, and body cell mass [ 19 , 20 ].…”
Section: Chronic Kidney Disease and Lean Body Massmentioning
confidence: 99%